Relato de experiência sobre a utilização de um vocalizador gratuito para dispositivos móveis em um centro de reabilitação - FIGUEIREDO JUNIOR, Jefferson Ferreira de (2020)
This work delivers a new version of a free mobile vocalizer on the Android plat-form called VoxLaPS and describes the experience of using it as a resource for color train-ing in a rehab center. Voicers are Assistive Technology tools that seek to offer Alternative Communication through graphic symbols, images, photographs, to people with disabilities that interfere with their ability to communicate (speech). Many voicers are available in the market, however, few are free and focused on the Portuguese language, which obviously hampers its use by a large part of the population. And this is the gap that this research seeks to mitigate. The second part of the paper shows an experience report on the use of the voicer proposed in the Calabrian Special Shelter (AEC) and the Special Reference Unit on Child Rehabilitation (URE-REI), where children and adolescents with neurological pathol-ogies are welcomed and cared for. In all, four previously selected children performed prac-tical activities, focusing on color learning, using VoxLaPS with the supervision of profes-sionals who work in the shelter. The author followed the sessions, that is, did not have any effective participation in the activities. Regarding the results, few gains were observed in relation to color learning due to the short time of use. However, the professionals consid-ered that the tool is a positive reinforcement in the treatment and no negative effect was observed in the use during the activities.